Antimicrobial Activity of [1,2,4]Triazolo[4,3-a]pyrimidine and New Pyrido[3,2-f][1,4]thiazepine Derivatives - Mohamed Ahmed, Mohamed S.; Farghaly, Thoraya A. (Letters in Organic Chemistry, 2018)
Background: The continued resistance of the body to antimicrobial drugs has led to the urgent need of preparing new heterogeneous compounds that are active antibacterial and antifungal. Methods: Two series of [1,2,4]triazolo[4,3-a]pyrimidines 8 and pyrido[3,2-f][1,4]thiazepines 12 were prepared in moderate to excellent yields through the reaction of pyrimidinethione 4 and pyridinethione 10 with the appropriate hydrazonoyl halides 5. Results: The elemental and spectral data of the newly synthesized compounds assured their structures. Also, the antimicrobial activity of the products was estimated and several derivatives exhibited promising activity. Conclusion: Two new series of triazolopyrimidine and pyridothiazepine have been synthesized via reaction of pyrimidinethione and pyridinethione with hydrazonoyl chlorides using triethylamine as basic reagent. The studied reaction was proved to be site selective since only one isolable product was obtained in each case. Moreover, the biological activity of the newly synthesized compounds was estimated against some microorganisms (bacteria and fungi) and the results gave promising activity compared with the standard compounds used.
Keywords: hydrazonoyl halides